Process for pressing Fe-Si-Al soft magnetic material
Through the improved ferrosilicon aluminum soft magnetic material pressing process, including powder mixing, press forming, sintering and heat treatment, the problems of long processing time, high cost and poor product performance in the existing process are solved, and more efficient and lower-cost material preparation is achieved, and the magnetic performance and stability of the product are improved.
Patent Information
- Application Number
- CN202510086462.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
AI Technical Summary
The existing ferrosilicon aluminum soft magnetic material pressing process has problems such as long processing time, high cost, poor product magnetic, density and density, resulting in poor product stability.
Improved process flow is adopted, including preparation of raw material powder, powder mixing, press molding, sintering processing, heat treatment, surface treatment and quality inspection. Specific steps include using Fe-Si-Al alloy powder, adding paraffin and talc as lubricant, mixing through a V-type mixer or a ball mill, designing a smooth mold, performing pre-pressing and main pressing, controlling the sintering temperature and time, performing annealing treatment, and surface coating and grinding of the material.
It improves the uniformity of the pressing process and the denseness of the finished product, improves the magnetic properties, density and mechanical strength of the material, reduces costs, and improves the stability of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic materials and powder metallurgy, in particular to a process for pressing sendust soft magnetic materials. Background Art
[0002] Iron-silicon-aluminum soft magnetic material (Fe-Si-Al alloy) is a kind of alloy material with good magnetic properties, which is widely used in electromagnetic equipment, sensors, transformers, transmission systems and other fields. Its main components are iron (Fe), silicon (Si) and aluminum (Al). The addition of silicon and aluminum can not only significantly improve the magnetic properties of the material, but also improve its corrosion resistance, thermal stability and mechanical strength.
[0003] With the rapid development of electronic technology, the market demand is increasing, and the requirements for high frequency, high power density, miniaturization and anti-electromagnetic interference of electronic devices are more prominent. This requires its core materials to develop in the direction of lower loss, higher DC bias capability and stable magnetic permeability. The existing process of pressing sendust soft magnetic materials has a long processing time and high cost, and the products produced have poor magnetism, density and compactness. The application in products leads to poor stability of the products. Here we propose a process for pressing sendust soft magnetic materials. Summary of the invention
[0004] In order to solve the above technical deficiencies, the present invention adopts a modified technical solution, a process for pressing sendust soft magnetic material, and the specific production steps include the following:
[0005] Step S1, raw material preparation, raw material powder, using Fe-Si-Al alloy powder;
[0006] Step S2, mixing the prepared raw materials into powder;
[0007] Step S3, pressing and molding, designing a mold according to the shape and size of the part, the mold is made of steel and has a smooth inner surface;
[0008] Step S4, sintering processing, sending the mold and raw materials into a furnace for heating treatment;
[0009] Step S5, heat treatment, annealing the sintered raw material;
[0010] Step S6, surface treatment is performed on the material, followed by post-processing such as grinding and quality inspection, and the processing is completed.
[0011] As a further preferred embodiment of the present invention, in step S1, the composition of the Fe-Si-Al alloy powder includes iron powder (Fe) accounting for 70%-85%, silicon powder (Si) accounting for 5%-15%, and aluminum powder (Al) accounting for 5%-10%. The powder particle size is usually between 20-100 microns and also includes a lubricant, and the composition of the lubricant is paraffin 0.5%-2% and talc 0-1%.
[0012] As a further preferred embodiment of the present invention, in step S2, the Fe-Si-Al powder is fully mixed with the lubricant for 30-60 minutes using a V-type mixer or a ball mill.
[0013] As a further preferred embodiment of the present invention, in step S3, the specific pressing includes the following steps: first, powder filling, accurately calculating the required amount of powder according to the size and shape of the parts, using automated equipment for filling, and then pre-pressing, the pressure is usually set between 100-200MPa, and after completion, the main pressing is performed, the pressing pressure is set between 300-600MPa, the pressing temperature is controlled at 20-42°C, and the pressing time: each pressing time is usually between 2-5 seconds.
[0014] As a further preferred embodiment of the present invention, in step S4, the sintering temperature: the sintering temperature is usually set between 1000-1400°C, the sintering process generally lasts for 1-2 hours, the atmosphere is controlled, and a reducing atmosphere is often used during sintering, and the reducing atmosphere includes nitrogen and hydrogen.
[0015] As a further preferred embodiment of the present invention, in step S5, the annealing temperature is usually set between 800-1000° C., and then helium or argon is introduced into the vacuum furnace, and the annealing time is controlled between 45-90 minutes.
[0016] As a further preferred embodiment of the present invention, in step S6, the surface of the material is subjected to coating treatment, wherein the coating includes nickel plating, zinc plating or phosphating, and the coating thickness is controlled between 5-20 microns, and the electroplating spraying method is used.
[0017] As a further preferred embodiment of the present invention, in step S6, the processing methods include external cylindrical grinding and internal cylindrical grinding, the size is controlled within ±0.1 mm, and density detection is performed after completion. The density and compactness of the parts are checked using the Archimedean method or X-ray CT scanning, and the hardness test is performed using a Rockwell hardness tester, and the magnetic permeability of the material is measured using a vibrating sample magnetometer (VSM).
[0018] Beneficial Effects
[0019] The present invention provides a process for pressing sendust soft magnetic material. It has the following beneficial effects:
[0020] In the powder mixing process of the present invention, paraffin wax and talcum powder are used as lubricants to ensure the fluidity of the powder and good filling property during the pressing process, which is helpful to improve the uniformity during the pressing process and avoid cracks or uneven density problems in the finished product. The V-type mixer or ball mill mixing equipment can effectively ensure the uniform distribution of the lubricant and the powder, improve the quality and consistency of the mixing, and thus improve the subsequent pressing quality. By setting the pressing process of the pre-pressing and main pressing stages, the parts can be preliminarily pressed and finally formed respectively to ensure the quality and dimensional accuracy of the parts. The strict control of the sintering temperature and time, and the use of a reducing atmosphere for sintering are helpful to eliminate the oxide layer and obtain higher material density. The temperature and atmosphere control of the annealing treatment can further eliminate the internal stress of the material, improve the magnetic properties, and simultaneously improve the toughness and mechanical strength of the material. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The present invention provides a technical solution: a process for pressing an AlSiFe soft magnetic material, wherein the specific production steps include the following:
[0023] Step S1, raw material preparation, raw material powder, using Fe-Si-Al alloy powder;
[0024] Step S2, mixing the prepared raw materials into powder;
[0025] Step S3, pressing and molding, designing a mold according to the shape and size of the part, the mold is made of steel and has a smooth inner surface;
[0026] Step S4, sintering processing, sending the mold and raw materials into a furnace for heating treatment;
[0027] Step S5, heat treatment, annealing the sintered raw material;
[0028] Step S6, surface treatment is performed on the material, followed by post-processing such as grinding and quality inspection, and the processing is completed.
[0029] In step S1, the composition of the Fe-Si-Al alloy powder includes iron powder (Fe) accounting for 70%-85%, silicon powder (Si) accounting for 5%-15%, and aluminum powder (Al) accounting for 5%-10%. The powder particle size is usually between 20-100 microns and also includes a lubricant. The composition of the lubricant is paraffin 0.5%-2% and talc 0-1%.
[0030] In step S2, the Fe-Si-Al powder and the lubricant are fully mixed for 30-60 minutes using a V-type mixer or a ball mill.
[0031] In step S3, the specific pressing includes the following steps: first, powder filling, according to the size and shape of the parts, accurately calculate the required amount of powder, use automated equipment for filling, and then pre-pressing, the pressure is usually set between 100-200MPa, after completion, the main pressing is carried out, the pressing pressure is set between 300-600MPa, the pressing temperature is controlled at 20-42°C, and the pressing time: each pressing time is usually between 2-5 seconds.
[0032] In step S4, sintering temperature: the sintering temperature is usually set between 1000-1400°C, the sintering process usually lasts for 1-2 hours, and the atmosphere is controlled. A reducing atmosphere is often used during sintering, and the reducing atmosphere includes nitrogen and hydrogen.
[0033] In step S5, the annealing temperature is usually set between 800-1000°C, and then helium or argon is introduced into the vacuum furnace, and the annealing time is controlled between 45-90 minutes.
[0034] In step S6, the surface of the material is subjected to coating treatment, wherein the coating includes nickel plating, zinc plating or phosphating, and the coating thickness is controlled between 5-20 microns by an electroplating spraying method.
[0035] In step S6, the processing methods include external cylindrical grinding and internal cylindrical grinding, the size is controlled within ±0.1mm, and density detection is performed after completion. The density and compactness of the parts are checked using the Archimedean method or X-ray CT scanning, and the hardness test is performed using a Rockwell hardness tester, and the magnetic permeability of the material is measured using a vibrating sample magnetometer (VSM).
[0036] Embodiment 1
[0037] A process for pressing a sendust soft magnetic material, the specific production steps include the following:
[0038] The raw material powder uses Fe-Si-Al alloy powder, the composition of which includes iron powder (Fe) accounting for 85%, silicon powder (Si) accounting for 9%, aluminum powder (Al) accounting for 5%, and the powder particle size is usually between 20-100 microns. It also includes a lubricant, and the composition of the lubricant is paraffin 0.5% and talc powder 0.5%;
[0039] The Fe-Si-Al powder and the lubricant were fully mixed for 60 minutes using a V-type mixer;
[0040] Pressing molding, the specific pressing includes the following steps: first, powder filling, according to the size and shape of the parts, accurately calculate the required amount of powder, use automated equipment to fill, and then pre-press, the pressure is usually set at 200MPa, after completion, the main pressing, the pressing pressure is set at 600MPa, the pressing temperature is controlled at 42℃, pressing time: each pressing time is usually 5 seconds;
[0041] Sintering process, the sintering temperature is usually set at 1400 ° C, the sintering process usually lasts for 2 hours, and the atmosphere is controlled. A reducing atmosphere is often used during sintering, and the reducing atmosphere includes nitrogen and hydrogen;
[0042] Heat treatment: annealing the sintered raw materials. The annealing temperature is usually set between 1000℃, and then helium is introduced into the vacuum furnace. The annealing time is controlled at 90min.
[0043] The material is surface treated and coated, the coating includes nickel plating, zinc plating or phosphating, the coating thickness is controlled at 20 microns, the electroplating spraying method, the processing methods include external cylindrical grinding and internal cylindrical grinding, the size is controlled within ±0.1mm, and density detection is performed after completion, the density and compactness of the parts are checked using the Archimedes method or X-ray CT scanning, the hardness test is performed using a Rockwell hardness tester, and the magnetic permeability of the material is determined using a vibrating sample magnetometer (VSM).
[0044] Performance, magnetic permeability (μ): -10000
[0045] Coercive force (Hc): 20A / m
[0046] Saturation magnetization: 1.5T.
[0047] Embodiment 2
[0048] A process for pressing a sendust soft magnetic material, the specific production steps include the following:
[0049] The raw material powder uses Fe-Si-Al alloy powder, the composition of which includes iron powder (Fe) accounting for 75%, silicon powder (Si) accounting for 15%, aluminum powder (Al) accounting for 8%, and the powder particle size is usually 20 microns. It also includes a lubricant, and the composition of the lubricant is 1% paraffin and 1% talc;
[0050] The Fe-Si-Al powder and the lubricant were fully mixed for 30 minutes using a ball mill;
[0051] Pressing molding, the specific pressing includes the following steps: first, powder filling, according to the size and shape of the parts, accurately calculate the required amount of powder, use automated equipment to fill, and then pre-press, the pressure is usually set at 100MPa, after completion, the main pressing, the pressing pressure is set at 300MPa, the pressing temperature is controlled at 20℃, pressing time: each pressing time is usually 2 seconds;
[0052] Sintering process, the sintering temperature is usually set between 1000℃, the sintering process usually lasts for 1 hour, and the atmosphere is controlled. A reducing atmosphere is often used during sintering, and the reducing atmosphere includes nitrogen and hydrogen;
[0053] Heat treatment: annealing the sintered raw materials. The annealing temperature is usually set between 800℃, and then argon gas is introduced into the vacuum furnace. The annealing time is controlled at 45min.
[0054] The material is surface treated and coated, the coating includes nickel plating, zinc plating or phosphating, the coating thickness is controlled at 5 microns, the electroplating spraying method, the processing methods include external cylindrical grinding and internal cylindrical grinding, the size is controlled within ±0.1mm, and density detection is performed after completion, the density and compactness of the parts are checked using the Archimedes method or X-ray CT scanning, the hardness test is performed using a Rockwell hardness tester, and the magnetic permeability of the material is determined using a vibrating sample magnetometer (VSM).
[0055] Performance, magnetic permeability (μ): 3000
[0056] Coercive force (Hc): 10A / m
[0057] Saturation magnetization: 1.0T.
[0058] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0059] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A process for pressing sendust soft magnetic material, characterized in that: The specific production steps include the following: Step S1, raw material preparation, raw material powder, using Fe-Si-Al alloy powder; Step S2, mixing the prepared raw materials into powder; Step S3, pressing and molding, designing a mold according to the shape and size of the part, the mold is made of steel and has a smooth inner surface; Step S4, sintering processing, sending the mold and raw materials into a furnace for heating treatment; Step S5, heat treatment, annealing the sintered raw material; Step S6, surface treatment is performed on the material, followed by post-processing such as grinding and quality inspection, and the processing is completed.
2. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S1, the composition of the Fe-Si-Al alloy powder includes iron powder (Fe) accounting for 70%-85%, silicon powder (Si) accounting for 5%-15%, and aluminum powder (Al) accounting for 5%-10%. The powder particle size is usually between 20-100 microns and also includes a lubricant. The composition of the lubricant is paraffin 0.5%-2% and talc 0-1%.
3. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S2, the Fe-Si-Al powder and the lubricant are fully mixed for 30-60 minutes using a V-type mixer or a ball mill.
4. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S3, the specific pressing includes the following steps: first, powder filling, according to the size and shape of the parts, accurately calculate the required amount of powder, use automated equipment for filling, and then pre-pressing, the pressure is usually set between 100-200MPa, after completion, the main pressing is carried out, the pressing pressure is set between 300-600MPa, the pressing temperature is controlled at 20-42°C, and the pressing time: each pressing time is usually between 2-5 seconds.
5. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S4, sintering temperature: the sintering temperature is usually set between 1000-1400°C, the sintering process usually lasts for 1-2 hours, and the atmosphere is controlled. A reducing atmosphere is often used during sintering, and the reducing atmosphere includes nitrogen and hydrogen.
6. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S5, the annealing temperature is usually set between 800-1000°C, and then helium or argon is introduced into the vacuum furnace, and the annealing time is controlled between 45-90 minutes.
7. The process for pressing a sendust soft magnetic material according to claim 1, characterized in that: In step S6, the surface of the material is subjected to coating treatment, wherein the coating includes nickel plating, zinc plating or phosphating, and the coating thickness is controlled between 5-20 microns by an electroplating spraying method.
8. The process for pressing Sendust soft magnetic material according to claim 1, characterized in that: In step S6, the processing methods include external cylindrical grinding and internal cylindrical grinding, the size is controlled within ±0.1mm, and density detection is performed after completion. The density and compactness of the parts are checked using the Archimedean method or X-ray CT scanning, and the hardness test is performed using a Rockwell hardness tester, and the magnetic permeability of the material is measured using a vibrating sample magnetometer (VSM).